PENGARUH PROFITABILITAS, SOLVABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN PERGANTIAN MANAJEMEN PADA AUDIT REPORT LAG PERUSAHAAN PERBANKAN - Artaningrum, Rai Gina; Budiartha, I Ketut; Wirakusuma, Made Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.03.TAHUN 2017, 2017)
This study aims to determine the effect of profitability, solvency, liquidity, size of company and management changes on audit report lag. The population in this study were banking companies listed in Indonesia Stock Exchange (BEI). The sample used in this study were selected by purposive sampling. Based on the criteria predefined sample of 41 banking companies listed in Indonesia Stock Exchange (BEI), 13 banking companies are eliminated that do not match the criteria that have been set and finnaly only 28 companies qualified. To test how the influence of the independent variables on the dependent variables used technique of multiple regression analysis. The results showed that the profitability, liquidity, firm size negatively affect audit report lag while solvency and management turnover positive effect on audit report lag.
Keywords: profitability, solvency, liquidity, company size, turnover Management, Audit Report Lag